2010
DOI: 10.1093/ije/dyp374
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the optimal recall period for disease symptoms in home-based morbidity surveillance in rural and urban Kenya

Abstract: Background In African settings with poor access to health care, surveillance and surveys of disease burden are often done through home visits. The optimal recall period to capture data on symptoms and health utilization is unknown.Methods We collected illness data among 53 000 people during fortnightly home visits in rural and urban Kenya. Dates of cough, fever and diarrhoea in the past 2 weeks and health-seeking behaviour were recorded. Incidence rates were modelled using Poisson regression for data collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
150
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(155 citation statements)
references
References 21 publications
5
150
0
Order By: Relevance
“…It is well documented that using a two-week recall period understates disease status, resulting in bias. Some studies [22][23][24] have suggested that a twoday or three-day recall period will minimize this bias, but Arnold and others 25 reported that one week is optimal when accounting for bias and variance. Although the two-week recall period used in the DHS is not ideal, any bias in our results should be towards the null, as long as disease misclassification is unrelated to exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that using a two-week recall period understates disease status, resulting in bias. Some studies [22][23][24] have suggested that a twoday or three-day recall period will minimize this bias, but Arnold and others 25 reported that one week is optimal when accounting for bias and variance. Although the two-week recall period used in the DHS is not ideal, any bias in our results should be towards the null, as long as disease misclassification is unrelated to exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The infrequent assessment of diarrhea was another limitation; participants were asked about diarrhea at every 3-month visit, whereas research has shown that the most accurate recall of morbidity events is in the last 3 days. 32 Diarrhea among household members was also ascertained from the HIV-positive participants who may or may not have been aware of diarrhea episodes among all household members, possibly resulting in underreporting of household diarrhea. Although the infrequent ascertainment of self-reported and household diarrhea by only a single household member may have been imprecise, the imprecision within a given household is unlikely to differ between time points; because the analytic comparisons were made within households, we do not believe that differential bias occurred.…”
Section: Discussionmentioning
confidence: 99%
“…This programme offers free, high-quality health care to participants, which promotes greater health care utilization. 16,17 The variability in findings between health facilities highlights the limitations of using one sentinel hospital to draw conclusions about the epidemiology and burden of influenza in a given district.…”
Section: Discussionmentioning
confidence: 99%
“…15 In one part of Bondo district, 25 000 people are offered free, high-quality care at Lwak Mission Hospital, including admission, as part of population-based infectious disease surveillance. 16,17 Influenza vaccination is…”
Section: Study Sitementioning
confidence: 99%